Analysis of the Village Head Replacement Mechanism Based on Law Number 6 of 2014 concerning Villages and Derivative Regulations - Suryaningsih, Suryaningsih; Krisnawansyah, Yahya; Zamhasari, Zamhasari; Gafar, Tengku Fahrul; Octavia, Santi (LPPM Universitas Ekasakti, 2023)
Law no. 6 of 2014 concerning villages regulates the appointment and dismissal of village heads. In carrying out the mandate for 6 years, it cannot be denied that along the way the village head will die, resign or be dismissed for one reason or another. Law no. 6/2014 does not regulate in detail the mechanism for replacing the village head. The replacement mechanism is regulated in derivative regulations, such as government regulations (PP) and several Minister of Home Affairs regulations. This article will analyze the mechanism for replacing village heads as regulated in the village law and its derivatives. The results of the research show that Law no. 6 of 2014 and its derivative regulations stipulate that if the village head dies, resigns from his position, and fulfills one of the conditions for being dismissed, the BPD reports to the regent via the sub-district head. The regent/mayor will make a decision to permanently dismiss the village head. The replacement of the village head then looks at 2 things, firstly, if the remaining term of office of the dismissed village head is less than 1 year, then leadership in the village will be held by the acting village head until the village head election. However, if the remaining term of office of the village head is more than 1 year, then leadership in the village is held by the acting village head until the village head is elected at the village meeting.